Analisis Pemakaian Mesin Jet Grout pada Proyek The Manhattan Mall & Condominium Medan - Dharma Sembiring; Davin Lois (Universitas Quality, 2018)
This study’s purposes to find data about jet grout usage on The Manhattan Mall & Condominium project – Medan. This study is done to gather a relationship between SPT N value to jet grout usage also the failure reason, this data is the result of the earth geotechnical and ground study report. As a part of the development planning The Manhattan Mall & Condominium – Medan, very important to know the profile and the characteristic of the soil at the site where the bulding will be builded. Therefore, it is necessary to study the soil as a calculate and to uo the success rate of jet grout usage when grouting. Data from study result of the soil is to get important information to the owner and planners to decrease the usage of jet grout machine.